1999
DOI: 10.1021/ma990470h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Molecular Weight on the Dynamics of the Conformational Transition of Poly(methacrylic acid)

Abstract: Stop flow pH jump experiments were carried out on poly(methacrylic acid), PMA, solution of various molecular weights. The fluorescence changes of the probe pyrene, which can locate in the hydrophobic PMA coil or in the aqueous phase, were used to monitor pH-induced events in the PMAwater system. At least two well-separated time regions for the pH-induced conformational change of PMA were observed: one with τ ) 1-2 s and another with τ ) 50-100 s. A theoretical model to quantitatively explain the observed kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
2
17
0
1
Order By: Relevance
“…Consequently, the excimer emission was not observed for the diluted polymer systems. We have to mention, however, that in a more recent study of Olea et al [26] an increasing excimer band was observed at pH . 5 for 0.01 mol dm 23 PMA/ 2 mmol dm 23 P solutions containing 0.1 mol dm 23 NaCl, and the I 1 =I 3 ratio in the high pH range was lower than in the absence of salt.…”
Section: Homopolymer Solutionsmentioning
confidence: 64%
“…Consequently, the excimer emission was not observed for the diluted polymer systems. We have to mention, however, that in a more recent study of Olea et al [26] an increasing excimer band was observed at pH . 5 for 0.01 mol dm 23 PMA/ 2 mmol dm 23 P solutions containing 0.1 mol dm 23 NaCl, and the I 1 =I 3 ratio in the high pH range was lower than in the absence of salt.…”
Section: Homopolymer Solutionsmentioning
confidence: 64%
“…[16]) or post-synthesis, a polyelectrolyte solution can be doped with fluorescent material [6,[17][18][19][20][21]. A luminescent species may be incorporated into the macromolecule either during polymerization (see e.g., Ref.…”
Section: Probes and Labelsmentioning
confidence: 99%
“…To achieve the latter, spectroscopists have exploited the fact that when in a coiled conformation in aqueous solution, certain polyelectrolytes can solubilize [6,12,[17][18][19][20][21] low molar organic molecules. On changing the pH, the chain expands releasing this material into the aqueous phase.…”
Section: Probes and Labelsmentioning
confidence: 99%
See 2 more Smart Citations